Early Detection of Visual Dysfunction in 5th and 6th Grade Readers Based on Head Movements and Head Position During Reading Activities. - Katoozi, Nikita; Coffey, Bradley (Optometry & Visual Performance, 2019)
Purpose: An investigation into the relationship between head movements while reading and visual dysfunction in children. This study was designed as an attempt to validate commonly held optometric beliefs that visual symptoms can manifest as head tilts, head movements, or head position close to reading material. Methods: Head movements were tracked with a webcam while 5th- and 6th-grade students, ages 10 and 11, were reading for fifteen minutes. Head movement behaviors were then compared to their vision screening results and a teacher observation checklist filled out by their classroom teachers. Results: A total of 24 subjects participated in the study. Head movement differences were subjectively noted between subjects, although objectively, no significant correlations were found between head movements, vision data, or the teacher observation checklist. Conclusion: The lack of literature in the area of head movements while reading and a child's visual system may be in part due to the difficulty of analyzing such behaviors objectively and habitually at the same time; alternatively, it may be because no such correlation is present.